Long-term Patient-Reported Outcomes After Surgery for Hypothenar Hammer Syndrome. (May 2020) - Demetri, Leah; Lans, Jonathan; Gottlieb, Rachel; Dyer, George S. M.; Eberlin, Kyle R.; Chen, Neal C.
Background: This study aims to describe the long-term patient-reported outcomes after surgery for hypothenar hammer syndrome (HTHS) and to identify factors associated with inferior outcomes.Methods: We retrospectively identified 27 patients who underwent surgical intervention for HTHS from 2002 to 2016. Fifteen patients (56%) completed outcome questionnaires: Quick Disabilities of the Arm, Shoulder, and Hand, Cold Intolerance Symptom Severity (CISS) survey, Patient-Reported Outcomes Measurement Information System Upper Extremity Computer Adaptive Test, and Patient-Reported Outcomes Measurement Information System Pain Interference Computer Adaptive Test. The median questionnaire follow-up was 7.2 years (interquartile range, 3.1-9.9). Outcomes were compared across different surgical techniques, and the influence of patient-related factors on outcomes was also evaluated.Results: Six (40%) patients experienced complete symptom resolution, 6 (40%) had improvement without complete resolution, 1 (7%) had resolution followed by recurrence, and 2 (13%) reported no improvement. The most common symptom after surgical intervention was cold intolerance. Questionnaire scores were similar across ligation, direct repair, and vein graft vascular reconstruction. Patients had better CISS scores if they had surgery on their nondominant hand (13.2 vs 38.6) and did not have a manual labor job (18.1 vs 40.5).Conclusions: Surgery for HTHS leads to moderate long-term improvement in patient-reported outcomes. Different surgical techniques yield similar symptomatic relief. Manual labor and surgery of the dominant hand are associated with worse CISS scores.